2015
DOI: 10.1063/1.4927219
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication analysis of interacting rigid cylindrical particles in confined shear flow

Abstract: Lubrication analysis is used to determine analytical expressions for the elements of the resistance matrix describing the interaction of two rigid cylindrical particles in two-dimensional shear flow in a symmetrically confined channel geometry. The developed model is valid for non-Brownian particles in a low-Reynolds-number flow between two sliding plates with thin gaps between the two particles and also between the particles and the walls. Using this analytical model, a comprehensive overview of the dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…A computation of forces on entrained particles during de-pinning indicated that, for the small nanoparticles studied here, drag forces due to liquid flow were below the resolution of the force calculation. This is in at least qualitative agreement with recent work [35] examining drag forces on immersed cylinders for varying separation distance between the cylinder and a substrate surface.…”
Section: For Highsupporting
confidence: 91%
See 2 more Smart Citations
“…A computation of forces on entrained particles during de-pinning indicated that, for the small nanoparticles studied here, drag forces due to liquid flow were below the resolution of the force calculation. This is in at least qualitative agreement with recent work [35] examining drag forces on immersed cylinders for varying separation distance between the cylinder and a substrate surface.…”
Section: For Highsupporting
confidence: 91%
“…Though our flow geometry is different here from the one studied in Ref. 35, sufficient similarity exists that we may expect drag forces to be small, despite the high flow rates observed in Figs. 8 and 9.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Again the total force is determined by the integration of this result. These coefficients produce the correct lubrication behaviour as d → [41,42].…”
Section: B Drag On Rods Near a Wallmentioning
confidence: 95%
“…This issue is also present in the simple case of rod by a single plane wall. In this case there exists asymptotic solutions in the limit that the separation is much larger then all lengths of the rod [35,40], the separation is much larger than the thickness of the rod but much smaller than the length [37] and the separations is of order of the thickness [41,42]. Furthermore each of these solutions were found using different asymptotic techniques; Brenner used the method of reflections to determine the drag when the separation is much larger than all lengths of the rod [40], Katz et al represented the body as a line of point forces above a wall [43] to determine the drag when the separation is larger than the thickness but smaller than the length [37], and Jeffrey and Onishi used lubrication arguments to determine the flow when an infinite cylinder is very close to the wall [42].…”
Section: Introductionmentioning
confidence: 99%